Algebra: A Combined Approach (4th Edition)

Published by Pearson
ISBN 10: 0321726391
ISBN 13: 978-0-32172-639-1

Chapter 7 - Review: 27



Work Step by Step

$\dfrac{4x-5}{3x^{2}}-\dfrac{2x+5}{3x^{2}}$ Evaluate the substraction: $\dfrac{4x-5}{3x^{2}}-\dfrac{2x+5}{3x^{2}}=\dfrac{(4x-5)-(2x+5)}{3x^{2}}=...$ $...=\dfrac{4x-5-2x-5}{3x^{2}}=\dfrac{2x-10}{3x^{2}}=...$ Take out common factor $2$ from the numerator to provide a more simplified answer: $...=\dfrac{2(x-5)}{3x^{2}}$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.